The Influence of Using Jigsaw as a Method on Students’ Reading Comprehension at the Seventh Grade of SMPN 7 Kota Serang - Nia Facharyani; Masrupi Masrupi; Eri Rahmawati (English Department - University of Sultan Ageng Tirtayasa, 2018)
The objective of this research was to find out the influence of using jigsaw on students’ reading comprehension. The researcher used quantitative research by using true experimental design for conducting the research. The sample of this research used cluster random sampling technique which is divided into two classes. The experiment class was VII B and VII F as control class with 38 students in each class. The instrument of this research was test which is divided into two parts; pre-test and post-test that given to both classes. The researcher used content validity and inter-rater reliability in order to make the instruments valid and reliable. The researcher used T-test formula to know the result. The result of the research showed that experiment class get mean score 59.34 in pre-test and 67.53 in post-test. Besides, students in control class got mean score 58.39 in pre-test and 64.29 in post-test. It shows that mean score of pre-test and post-test in experiment class is higher than control class. The calculation showed the result of tcount is higher than ttable (8.76 ≥ 1.99) with the significance 0.05. It can be concluded that there was influence of using jigsaw as a method on students’ reading comprehension at the seventh grade of SMPN 7 Kota Serang and it was proven.Keywords: jigsaw method; students’ reading comprehension